1995
DOI: 10.1029/94gl03050
|View full text |Cite
|
Sign up to set email alerts
|

Simulated annealing inversion of teleseismic P‐wave slowness and azimuth for crustal velocity structure at Long Valley Caldera

Abstract: Simulated annealing, a non‐linear global search algorithm, is used to invert teleseismic P‐wave slowness and azimuth data for crustal velocity structure. Synthetic tests show that simulated annealing is able to locate low P‐wave velocity zones with reasonable accuracy in space, and recovers almost 70% of the target velocity perturbations. Testing suggests that significant results can be obtained with as few as two stations. Inversion of ray direction data from Long Valley caldera finds an asymmetrical low velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…The impressive results stimulated many applications to other geophysical optimization problems. These include the estimation of Earth models from fitting of seismic body waveforms in exploration seismics reflection seismics and migration [ Jakobsen et al ., 1988; Jervis et al ., 1993; Varela et al ., 1998; Landa et al ., 1989; Mosegaard and Vestergaard , 1991; Vestergaard and Mosegaard , 1991; Sen and Stoffa , 1991]; inversion of travel/arrival time data [ Pullammanappallil and Louie , 1993, 1994]; earthquake location and rupture histories [ Billings , 1994; Hartzell and Liu , 1996]; seismic source and ground motion studies [ Scherbaum et al ., 1994; Courboulex et al ., 1996; Ihmle and Ruegg , 1997]; estimation of crustal structure [ Steck , 1995; Zhao et al ., 1996]; deconvolution of seismograms [ Courboulex et al ., 1996; Calderon et al ., 1997]; thermodynamic modeling [ Bina , 1998]; groundwater management and remediation [ Dougherty and Marryott , 1991; Kou et al ., 1992; Rizzo and Dougherty , 1996; Rogers et al ., 1998]; more residual statics estimation [ Vasudevan and Wilson , 1991; Nørmark and Mosegaard , 1993]; waste disposal site selection [ Muttiah et al ., 1996]; geostatistics [ Datta et al ., 1995; Goovaerts , 1996; Pardo , 1998]; seismic ray tracing [ Velis and Ulrych , 1996]; and electromagnetic, resistivity, and magnetotelluric imaging [ Gilbert and Virieux , 1991; Dosso and Oldenburg , 1991; Dittmer and Szymanski , 1995]. This is only a subset of the many papers making use of this technique over the past 10 years.…”
Section: A Brief History Of Monte Carlo Inversion In Geophysicsmentioning
confidence: 99%
“…The impressive results stimulated many applications to other geophysical optimization problems. These include the estimation of Earth models from fitting of seismic body waveforms in exploration seismics reflection seismics and migration [ Jakobsen et al ., 1988; Jervis et al ., 1993; Varela et al ., 1998; Landa et al ., 1989; Mosegaard and Vestergaard , 1991; Vestergaard and Mosegaard , 1991; Sen and Stoffa , 1991]; inversion of travel/arrival time data [ Pullammanappallil and Louie , 1993, 1994]; earthquake location and rupture histories [ Billings , 1994; Hartzell and Liu , 1996]; seismic source and ground motion studies [ Scherbaum et al ., 1994; Courboulex et al ., 1996; Ihmle and Ruegg , 1997]; estimation of crustal structure [ Steck , 1995; Zhao et al ., 1996]; deconvolution of seismograms [ Courboulex et al ., 1996; Calderon et al ., 1997]; thermodynamic modeling [ Bina , 1998]; groundwater management and remediation [ Dougherty and Marryott , 1991; Kou et al ., 1992; Rizzo and Dougherty , 1996; Rogers et al ., 1998]; more residual statics estimation [ Vasudevan and Wilson , 1991; Nørmark and Mosegaard , 1993]; waste disposal site selection [ Muttiah et al ., 1996]; geostatistics [ Datta et al ., 1995; Goovaerts , 1996; Pardo , 1998]; seismic ray tracing [ Velis and Ulrych , 1996]; and electromagnetic, resistivity, and magnetotelluric imaging [ Gilbert and Virieux , 1991; Dosso and Oldenburg , 1991; Dittmer and Szymanski , 1995]. This is only a subset of the many papers making use of this technique over the past 10 years.…”
Section: A Brief History Of Monte Carlo Inversion In Geophysicsmentioning
confidence: 99%
“…The source of previous inflation episodes has been suggested to be a combination of partially molten magma and hydrous fluids [ Hill , 2006], and there is no evidence to suggest this episode is different. The existence of partial melt at shallow depths in the LVC is supported by the volcanic history of LVC [ Bailey et al , 1976; Bailey , 1989], the seismic refraction data [ Hill , 1976; Hill et al , 1985], the tomographic inversions [ Dawson et al , 1990; Steck , 1995; Sanders et al , 1995; Weiland et al , 1995], and strongly suggested by changes in gravity associated with the 1997–1998 episode [ Battaglia et al , 1999].…”
Section: Analytical Modelsmentioning
confidence: 99%
“…Recently, genetic algorithms have been used to conduct inversions (Ammon & Vidale 1993; Steck 1995). They are non‐linear global search algorithms, which draw on similarities between combinatorial optimization and the statistical mechanics of crystallization.…”
Section: Advances Of Seismic Tomographymentioning
confidence: 99%
“…Seismic wave polarizations can be measured either with an array of stations or with a single 3‐component station. Recently, a few researchers have combined teleseismic polarization data with arrival times to conduct tomographic inversions and obtained promising results (Steck 1995; Hu et al 1994). The polarization inversion is not influenced by hypocentral errors and not sensitive to deep mantle velocity structure.…”
Section: Advances Of Seismic Tomographymentioning
confidence: 99%